Rethinking the Inequality-Growth Nexus: Short-Term Gains and Long-Term Challenges - Khanh Duong; Nguyen Phuc Van (Global Labor Organization (GLO), 2023)
This study reexamines the relationship between economic growth and inequality, challenging the conventional view that regards inequality solely as an impediment to development. While recognizing the essential role of economic growth in development plans, our analysis extends beyond this traditional focus, acknowledging that development encompasses more than just growth. We explore how inequality interplays with pressing global challenges like climate change and pandemics, areas that have garnered significant scholarly and political attention recently. Contrary to the prevalent belief, often reinforced by income redistribution policies, that inequality invariably hinders economic progress, our findings suggest a more nuanced reality. In the short term, an increase in inequality appears to boost growth in economies reliant on physical capital, whereas its impact on growth in human capital-intensive economies remains ambiguous. Over the long term, however, sustained inequality negatively affects both affluent and less affluent countries through the human capital channel, with a more pronounced impact on the latter. Our research indicates that short-term increases in inequality (within a five-year span) do not adversely affect economic growth, calling into question the necessity of stringent taxation measures. Nevertheless, persistent high inequality over longer periods (exceeding ten years) is linked to social instability. Hence, we advocate for the aggressive implementation of socially inclusive measures, such as enhanced education, healthcare, and fertility control, particularly in developing countries, to address these long-term challenges.
Keywords: D63; O15; O50; 330; Inequality; Economic growth; Human capital; Physical capital